Engaging learning: students' reactions to Quizizz in microeconomics classrooms - Othman, Muhammad Hanif; Mohd Rosli, Zouhair (2024)
Higher education plays a crucial role in shaping future generations (Othman et al., 2019). Therefore, it is imperative for institutions of higher learning to enhance their teaching methodologies by incorporating formative assessment. Formative assessment stands out as a highly effective strategy in educational improvement, advocated by scholars and educators as a fundamental element in teaching and learning (Veugen et al., 2021; Black & Wiliam, 2018; OECD, 2005). Despite its growing use in classrooms (Carless, 2017), studies reveal that formative assessment has not become commonplace in educational practices (Deneen et al., 2019; Kippers et al., 2018).